Problematika Talak Ba’in: Analisis Pembuktian Syarat-Syarat Pernikahan Kembali bagi Pasangan Pasca Talak Ba’in - Imani Fatikhah, Syal Syah; Muhamad Mustahal; Arifuat Marzuki (Kartika: Jurnal Studi Keislaman, 2026)
This research discusses the problems of talaq ba’in and proves the requirements for couples who wish to remarry after the talak occurs. Talak ba’in, whether sughra or kubra, has legal consequences that completely terminate the marital relationship so that reconciliation is not possible without fulfilling certain conditions. The focus of this research is to analyze fiqh provisions regarding talaq ba’in, remarriage requirements for divorced couples, as well as the evidentiary mechanisms implemented at the Purworejo Regency Religious Affairs Office (KUA). The research uses qualitative methods with a normative-sociological approach through interviews with rulers and studies of various sources of fiqh, statutory regulations, and the Compilation of Islamic Law (KHI). The research results show that proof of talak status at the KUA is carried out mainly through verification of the divorce certificate as authentic proof of divorce. Even though talak ba’in kubra cases are rare, the KUA still applies the principle of prudence in checking the validity of the legal status of prospective brides and grooms. This research concludes that the main problem lies in the aspect of formal verification of personal requirements, especially in talak ba’in kubra, as well as the importance of synergy between Islamic law and positive law in maintaining legal order and the validity of marriage in society.